2021
DOI: 10.3389/fpsyg.2021.679541
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Psychosocial Interventions for Elder Abuse in Community Settings: A Systematic Review and Meta-Analysis

Abstract: As a global public health concern, elder abuse negatively affects health, psychosocial wellbeing, and mortality among elders. Research and practice efforts made to explore effective prevention and intervention strategies are growing. Despite the growing number of intervention studies on elder abuse, research synthesis on the empirical literature seems lacking. This study aims to identify the pooled effect size of prevention and interventions targeted ultimate and intermediate outcomes for elder abuse that occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In addition to the review-of-reviews on the effectiveness of EM interventions (Marshall et al, 2020 ), we identified four additional scoping/systematic reviews or meta-analysis studies (Burnes et al, 2021 ; Kayser et al, 2021 ; Shen et al, 2021 ; Van Royen et al, 2020 ) relevant to EM intervention for a total of 92 distinct studies on EM interventions represented across the five reviewed papers. Details about these studies, including key findings and recommendations, are provided in Table 1 .…”
Section: Scoping Review Resultsmentioning
confidence: 99%
“…In addition to the review-of-reviews on the effectiveness of EM interventions (Marshall et al, 2020 ), we identified four additional scoping/systematic reviews or meta-analysis studies (Burnes et al, 2021 ; Kayser et al, 2021 ; Shen et al, 2021 ; Van Royen et al, 2020 ) relevant to EM intervention for a total of 92 distinct studies on EM interventions represented across the five reviewed papers. Details about these studies, including key findings and recommendations, are provided in Table 1 .…”
Section: Scoping Review Resultsmentioning
confidence: 99%
“…Although several reviews found that some interventions were successful in improving knowledge and attitudes about violence, these concluded that there was insufficient evidence on their effectiveness in reducing the extent of abuse [16,[40][41][42]. Nevertheless, the use of multiple approaches such as education and support services seemed to be effective, as a mixed approach showed significant effects [43]. Thus, interventions using mixed approaches may be more effective, especially if combined with the use of technology (e.g., wearables, monitoring systems) that could track episodes of violence while maintaining the privacy of patients and HCWs [44].…”
Section: Discussionmentioning
confidence: 99%
“…Future research on PIs should focus on the needs of older patients [ 54 ] and connections between intervention activities and ultimate change in behaviors related to abuse of older individuals [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multicomponent psychosocial intervention (PI) was evaluated as being effective in improving cognitive functioning, social interaction, and well-being [ 15 ] and in decreasing pain [ 16 ] among patients with dementia. A systematic review by Shen et al [ 17 ] supports the effectiveness of PIs combined with family-based models, education, supportive services for caregivers, and abuse of older individuals. Another study suggested that physical activity is positively correlated but sedentary behaviors are negatively associated with psychosocial well-being in early childhood [ 18 ].…”
Section: Introductionmentioning
confidence: 99%